PENGARUH KEPUASAN KERJA TERHADAP PRODUKTIVITAS KERJA PADA PEGAWAI DI KANTOR DINAS PENDIDIKAN DAN KEBUDAYAAN BULUKUMBA - Jaya, Ikhlazul Amal; Siti Hasbiah; Ruma, Zainal (DECISION : Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of job satisfaction on the work productivity of the Bulukumba Education and Culture Office employees. The population in this study were employees of the Bulukumba Education and Culture Office as many as 45 respondents. The number of samples is 45 employees of the Education and Culture Office of Bulukumba. The data analysis technique that the writer uses in this research is descriptive quantitative. The data collection used is by using a questionnaire given to respondents. The data is processed using SPSS 21.0 for windows. Then, based on the results of the study showed that the variable job satisfaction had a positive and significant effect on the work productivity of the Bulukumba Education and Culture Office employees. which means that the perceived job satisfaction can increase the productivity of an employee at work.